The impact of capital flows from commercial banks and FDI on sustainable economic growth in ASEAN countries - Long Thanh Tran (Contemporary Economics, 2022)
The paper is aimed at assessing the impact of capital flows from commercial banks and FDI on sustainable economic growth in ASEAN countries. The study has conducted quantitative secondary analysis on data collected from 1980 to 2018 for Thailand, Vietnam and Malaysia. Descriptive statistics, correlation and ARDL are applied to measure the impact of each variable on sustainable economic growth. The study has shown a significant long-run relationship of short-term debt, long-term debt, technology, capital flows and savings and investment on sustainable economic growth. Short-term debt is found to have a negative impact in the long run. The short-run relationship between long-term debt, short-term and sustainable economic growth is significant while insignificant for all other variables. The study is useful for countries that are aiming for sustainable economic growth since all the factors are helpful to consider. Future researchers can use other regions to empirically examine the same model. The study is focused on only 3 countries from ASEAN countries and is only focused on one region. As economic and political scenarios different, results might not be same in other parts of the world.
Keywords: F21; O11; C33; 330; capital flow; foreign direct investment; sustainable economic growth; ARDL